Prevalence of rumen impaction with non-biodegrable materials in cattle in Ibadan, Nigeria (2012)
A study was conducted on 3031 cattle slaughtered in Ibadan over a period of three months to determine the prevalence of rumen impaction with indigestible garbage and evaluate breed, sex, age and some blood indices as risk factors. Thorough antemortem and postmortem examinations were carried out on each of the animals to determine the breed, health status, sex, age and presence of indigestible garbage in the rumen while blood samples were collected and analysed only for animals with indigestible garbage, to determine total serum protein and phosphorus levels. Results showed overall prevalence of rumen impaction was 10.77% and it differed significantly between breeds, but was highest in the Red Bororo (RB). Sex and age had significant influence on the prevalence of rumen impaction. It was significantly higher (P < 0.05) in females than in males and in older animals than in younger ones. Total serum protein and phosphorus levels were significantly lower than reference values in animals with rumen impaction.